(3TQM GdcTGas - (3CMeO Hf GdMSf Hf jhSa, aNQ GdOjf GdLGQHQOj , (B746 (3g` s; (3aNQ GdOjf CMeO Hf MSjf Hf jhSa GdLGQHQOj, GdLGQHQOj,J (B746 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi EfYGeg eRjO EaVGdg hEcQGeg hCSJeOg GdJhajb ddTQhY ai cJGH JJeI GdcTGa hEJeGeg s
(3BNQgG (B:s
(( (3hdbO YdeJe GdPjf GYJOhG efce ai GdSHJ (B)) (3deG bGd dge (B(((3chfhG bQOI (B)) (3UGQhG cPdc Cj deG CQGO Hge Pdc UGQhG ceG CQGO s
(3GdfSNI HgG MhGTs
(3HYV GddhMGJ SjFI GdJUhjQs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdfSNI HGcKQ ef bde s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJaSjQ hYdhe GdbQBfs